Ablation of transient receptor potential vanilloid subtype 1-expressing neurons in rat trigeminal ganglia aggravated bone resorption in periodontitis with diabetes. (January 2022) - Zhang, Bo; Yang, Yang; Yi, Jianru; Zhao, Zhihe; Ye, Rui
Abstract: Objectives: We aimed to investigate the contribution of neurons expressing transient receptor potential vanilloid subtype 1 (TRPV1) to alveolar bone homeostasis in periodontitis with diabetes. Design: Diabetes was induced by streptozotocin injection in Sprague-Dawley rats. Resiniferatoxin was injected into left trigeminal ganglia to ablate TRPV1-expressing neurons. 3–0 silks were tied around left maxillary second molars to induce experimental periodontitis. Alveolar bone was assessed by micro-computed tomography and tartrate-resistant acid phosphatase staining. Macrophages were detected by immunohistochemistry staining. Results: TRPV1 expression in trigeminal ganglia was increased in diabetic rats compared to non-diabetic counterparts. Local ablation of TRPV1 eliminated facial heat hyperalgesia but aggravated alveolar bone damage and osteoclastogenesis in experimental periodontitis in both diabetic and non-diabetic rats. Immunohistochemistry staining presented enhanced macrophage infiltration and M1 macrophage polarization in periodontal lesions in TRPV1-ablated groups. Conclusions: These findings demonstrated that TRPV1 expression in trigeminal ganglia could be enhanced in diabetic condition, and the integrity of TRPV1-expressing neurons in trigeminal ganglia exerted a neuroprotective effect against alveolar bone resorption and inflammation in diabetic periodontitis. Highlights: The study concerned transient receptor potential vanilloid subtype 1 (TRPV1) receptors. TRPV1 expression in trigeminal ganglia was increased in rats with diabetes. Intraganglionar ablation of TRPV1-positive neurons aggravated diabetic periodontitis. Ablation of TRPV1-positive neurons promoted M1 macrophage polarization.